Determinants of perception toward life insurance and its impact on intention to purchase - Thien, Sang Lim; Dayang Zuraini Dzulkifli; Zaiton Osman; Rosle Mohidin; Amer Azlan Abdul Jamal (Penerbit UMS, 2020)
Life insurance is one of the solutions for managing personal financial risks. It is effective in protecting surviving individuals of families against loss of income resulting from the premature death of bread providers. This study aims to investigate the explanatory factors influencing perception toward life insurance. The research was underpinned by the Perception Formation Model and further supported results of previous findings. Using primary data drawn from respondents up to the age of 35 years old, results based on Variance-based Structural Equation Modelling (SEM) suggested intention to purchase life insurance was related by how people perceive the product itself. As expected, those who favorably perceive life insurance have more inclination to purchase. The resultant outcomes suggested social influence agents, including family members, peers and the Internet significantly explain peoples’ perception toward life insurance. The study implicated industry players in terms of the design of marketing mix and shed lights in better understanding of the complexity in the decision-making process with regards to life insurance purchase intention.